Correlation between malnutrition and health-related quality of life (HRQOL) in elderly Iranian adults. Issue 1 (January 2020) - Khatami, Fatemeh; Shafiee, Gita; Kamali, Koorosh; Ebrahimi, Mehdi; Azimi, Mahinsadat; Ahadi, Zeinab; Sharifi, Farshad; Tanjani, Parisa Taheri; Heshmat, Ramin
Objectives: We aimed to evaluate the association of nutritional status and health-related quality of life (HRQOL) among elderly Iranian residents. Methods: We used the 36-item Short Form Health Survey (SF-36) to assess HRQOL among participants with normal nutrition status, at risk of malnutrition, and malnourished. Results: Mean group scores for the Physical Component Summary (PCS) of the SF-36 were 44, 36.5, and 29.0 for normal, at-risk, and malnourished groups, respectively; for the Mental Component Summary (MCS), these were 47.1, 40.7, and 34.8, respectively. The PCS and MCS displayed significant positive correlation with malnutrition in three models: crude (I); age- and sex-adjusted (II); and adjusted for age, sex, education, occupation, marital status, and residence. Standardized beta coefficients of PCS in Models I–III were 1.35, 1.27, and 1.14, respectively; for MCS, these were 1.11 in all three models; all results were statistically significant. Estimated results of logistic regression were −6.023 for malnourished versus well-nourished and −2.652 for malnourished versus at risk of malnutrition. Conclusion: Our analyses revealed the crucial impact of nutritional status on both mental and physical components of HRQOL.